Persepsi Generasi Muda Terhadap Pekerjaan Sebagai Petani Di Desa Sion Kecamatan Tompaso Baru Kabupaten Minahasa Selatan - Singal, Aldi Gabriel; Baroleh, Jenny; Memah, Melsje Yelly (Sam Ratulangi University, 2024)
The aim of this research is to find out and describe the perceptions of the younger generation towards work as farmers in Sion Village, Tompaso Baru District, South Minahasa Regency. The research took place from June to August 2023. The data collected is primary data obtained by direct interviews with youth in Sion Village using a questionnaire. Secondary data was taken from village and sub-district offices as well as research reports, journals and from the internet related to this research. The sample was chosen deliberately (purposive sampling) to represent the entire younger generation, totaling 30 respondents, namely young people aged 17 to 30 years (who are not yet married). The results of the research show that the young generation in Sion Village has a good perception of work as farmers with parental support for the young generation to continue the family farming business, supported by the government which also supports the young generation to farm, although the young generation is aware that land ownership influences younger generation to farm, the risk of failure in farming is less, but the perception of work as farmers in Sion Village for the younger generation is quite good.